Employing artificial intelligence technologies to improve the efficiency of paramedic training programs in the Kingdom of Saudi Arabia: a descriptive and analytical study (The Review of Diabetic Studies, 2025)
This study aims to investigate the role of employing artificial intelligence technologies in improving the efficiency of paramedic training programs in the Kingdom of Saudi Arabia. It relied on the descriptive analytical approach and was based on an electronic questionnaire applied to a sample of (200) participants working in the field of emergency and health training. The results revealed that artificial intelligence significantly contributes to the design of more interactive and realistic training programs, improves the speed and accuracy of paramedic responses in emergency situations, and provides accurate and immediate feedback to trainees and enhances decision-making skills during critical situations. The results also showed that artificial intelligence helps identify each trainee's needs individually and increases the efficiency of practical training compared to traditional methods. It also contributes to reducing costs in the long term and enabling the simulation of rare and complex situations that are difficult to provide in real-life training. The results also confirmed that the use of artificial intelligence enhances the motivation and self-confidence of trainees and raises their overall performance level, which was reflected in the rise in the arithmetic averages of all items above the neutral value (3) on the Likert scale, with high internal consistency of the measurement tool (Cronbach's alpha = 0.91). Accordingly, the study recommends expanding the integration of artificial intelligence technologies into paramedic training programs, developing advanced simulation systems that reflect rare and critical medical situations, and creating interactive digital training platforms that enhance training efficiency and reduce costs. It also recommends adopting educational and health policies that support technological innovation in line with the goals of Saudi Vision 2030.